TIME CDST: an updated tool to address the current challenges in wound care. (3rd March 2019) - Moore, Zena; Dowsett, Caroline; Smith, Glenn; Atkin, Leanne; Bain, Michael; Lahmann, Nils A.; Schultz, Gregory S.; Swanson, Terry; Vowden, Peter; Weir, Dot; Zmuda, Ann; Jaimes, Henry
Abstract : Despite the understanding that wounds are a common problem affecting the individual, the health service and society as a whole, there continues to be a lack of a systematic, structured, evidence-based approach to wound management. The TIME principle was first published in 2003, 1 and has since been integrated by many into clinical practice and research. However, this tool has been criticised for its tendency to focus mainly on the wound rather than on the wider issues that the patient is presenting with. At an expert meeting held in London in 2018, this conundrum was addressed and the TIME clinical decision support tool (CDST) was elaborated upon. This article introduces the TIME CDST, explains why it is required and describes how its use is likely to benefit patients, clinicians and health-service organisations. It also explores the framework in detail, and shows why this simple and accessible framework is robust enough to facilitate consistency in the delivery of wound care and better patient outcomes. Finally, it outlines the next steps for the rollout, use and evaluation of the impact of the TIME CDST.